Estimation of agricultural production statistics - a project proposal - Instituto Interamericano de Ciencias Agrícolas (IICA) (Instituto Interamericano de Ciencias Agrícolas (IICA), 2022)
This document shows the development and production of statistical estimates using as a basis, the poulation frame development by the resourse development and planning division and provision of a training programme on basic statistics, survey methods and interviewers methodology.